2002
DOI: 10.1002/ana.10069
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of choline acetyltransferase activity in hippocampus and frontal cortex of elderly subjects with mild cognitive impairment

Abstract: In Alzheimer's disease (AD), loss of cortical and hippocampal choline acetyltransferase (ChAT) activity has been correlated with dementia severity and disease duration, and it forms the basis for current therapies. However, the extent to which reductions in ChAT activity are associated with early cognitive decline has not been well established. We quantified ChAT activity in the hippocampus and four cortical regions (superior frontal, inferior parietal, superior temporal, and anterior cingulate) of 58 individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
405
3
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 641 publications
(447 citation statements)
references
References 72 publications
35
405
3
4
Order By: Relevance
“…Some recent investigations also suggest that cholinergic abnormalities, as measured by reductions in the neocortical activity of the cholinergic marker enzymes, ChAT and AchE, may not be an early pathophysiological event in AD (Davis et al, 1999;Tiraboschi et al, 2000). Additionally, a study in individuals with mild cognitive impairment actually found an upregulation of ChAT activity in the hippocampus and frontal cortex of this population (DeKosky et al, 2002). It should be noted that the findings from these studies are derived from post-mortem observations.…”
Section: Discussionmentioning
confidence: 91%
“…Some recent investigations also suggest that cholinergic abnormalities, as measured by reductions in the neocortical activity of the cholinergic marker enzymes, ChAT and AchE, may not be an early pathophysiological event in AD (Davis et al, 1999;Tiraboschi et al, 2000). Additionally, a study in individuals with mild cognitive impairment actually found an upregulation of ChAT activity in the hippocampus and frontal cortex of this population (DeKosky et al, 2002). It should be noted that the findings from these studies are derived from post-mortem observations.…”
Section: Discussionmentioning
confidence: 91%
“…75,76 A comparison between these cases and those that have a similar pathological load but a diagnosis of AD may help differentiate factors crucial to cognitive function from those less directly applicable, such as cognitive reserve or neuroplasticity. 79 The pathological variability found in the MCI cases may also have been a reason that the increase in specific tau inclusions did not significantly differ among clinical diagnosis. MCI is characterized by the presence of memory deficits that are not severe enough to curtail activities of daily living or to meet the criteria for dementia, 80 but that are considered to represent a prodromal stage of AD.…”
Section: Discrepancy Between Clinical Diagnosis and Neuropathologicalmentioning
confidence: 94%
“…Previous studies have shown that acetylcholine can modulate the activity of auditory cortex (Buchwald et al, 1991;Metherate, 2004). There is also an increase in cholinergic enzyme activity in certain cortical regions in MCI (Dekosky et al, 2002). Thus, changes in the cholinergic system may be associated with the modulation of auditory cortical activities in MCI and Alzheimer's disease.…”
Section: Cholinergic Transmission and The Long-latency P50 Component mentioning
confidence: 94%
“…b-amyloid plaques, neurofibrillary tangles) gradually accumulate in the brain without sufficient neuronal damage to cause clinically detectable dementia (Giannakopoulos et al, 2003;Ohm et al, 1995). Neuropathological studies report that both the extent of neuronal loss (Kordower et al, 2001) and the regional accumulation of b-amyloid plaques and neurofibrillary tangles (Dekosky et al, 2002;Mufson et al, 1999) in MCI are similar to early Alzheimer's disease. Taken together, the greater risk of Alzheimer's disease in MCI and the similarity in neuropathological features to early Alzheimer's disease suggests that MCI can be a transition state between normal aging and Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%